Kepemimpinan Transformasional Kepala Sekolah dalam Mendorong Inovasi Pembelajaran di Sekolah Dasar - Dyan Erlisa (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to analyse the influence of principals' transformational leadership in promoting learning innovation in primary schools. Transformational leadership, which involves motivating, professional development and empowering teachers, is considered to create an environment that supports innovation in learning. This research uses a descriptive qualitative approach with data collection through in-depth interviews, observations, and documentation studies in several primary schools. The results show that principals who apply transformational leadership play an important role in encouraging teachers to innovate in developing learning methods. In addition, principals are also able to build close collaboration between teachers, creating a community that supports each other in an effort to improve the quality of learning. In practice, effective principals are able to overcome challenges in implementing learning innovations, despite resistance to change and limited resources. This research shows that transformational leadership not only impacts on teacher motivation and engagement, but also on improving student learning outcomes. The findings provide a strong basis for the development of transformational leadership in primary schools and its relevance in the evolving educational context. Further research is expected to explore more deeply the external factors that influence the successful implementation of innovations, such as education policy and community support.